Polystyrene microplastic particles: In vivo and in vitro ocular surface toxicity assessment. (15th June 2022) - Zhou, Xiaoping; Wang, Guoliang; An, Xiaoya; Wu, Jun; Fan, Kai; Xu, Lina; Li, Cheng; Xue, Yuhua
Abstract: Microplastics (MPs) have become a global concern as a key environmental pollutant. MPs are widely found in oceans, rivers, bottled water, plastic-packaged foods, and toiletries. The ocular surface is the exposed mucosal tissue, which comes in contact with MP particles contained in toiletries, tap water, cosmetics, and air. However, the effects of MPs on ocular surface health are still unclear. In this study, the toxic effects of polystyrene MPs (PS-MPs) on the ocular surface in vivo and in vitro were explored. The results demonstrated that 50 nm or 2 μm PS-MPs, following exposure for 48 h appeared in the cytoplasm of two kinds of eye cells in vitro and caused a concentration dependent reduction in cell viability, further causing oxidative stress and cell apoptosis. In addition, after treatment for 2 or 4 weeks, 50 nm and 2 μm PS-MPs were deposited in the conjunctival sac of mice. After 2 and 4 weeks of PS-MP treatment, the number of goblet cells in the lower eyelid conjunctival sac decreased to 65% and 40% of that in the control group, respectively. Moreover, dry eye like ocular surface damage and inflammation of conjunctiva and lacrimal gland in mice were observed. In conclusion, this study revealed that PS-MPs could cause ocular surface dysfunctions in mice, thus providing a new perspective for the toxic effects of MPs on ocular surface. Graphical abstract: Image 1 Highlights: PS-MPs could enter the HCECs and HConjECs in vitro. PS-MPs caused oxidative stress and apoptosis of HCECs. Dry eye like ocular surface damage occurred in mice after exposure to PS-MPs. PS-MPs induced the decrease of conjunctival goblet cells and tear levels in vivo. PS-MPs caused inflammation of the conjunctiva and lacrimal gland.